Attraversare la scena. Lisetta Carmi fotografa di teatro (1962-1967) - Cristiana Sorrentino (Drammaturgia)
Between 1962 and 1967, in the first phase of her professional career, Lisetta Carmi took part in the theatrical experiences as stage photographer in Genoa: firstly, in the Teatro Stabile, then close to Carlo Quartucci and other protagonists of experimental theatre of those years. In this context, Carmi found in theatre an important place to practice photography, as well as an opportunity for her own language to grow up. From theatre, she got theoretical and visual nourishment also for her social projects. Starting from an analysis of some photo-textual contributions published in magazines such as «Popular Photography italiana» and «Sipario», this essay aims at proposing an original interpretation of Carmi’s photographic work related to theatre, and above all to experimental performances, so far never completely discussed by historiography. According to this perspective, theatre represents for Carmi not only a subject to be observed, but a place of dialogue and exchange; a theoretical device, which is complementary to photography, for building a common field of research and investigation.